Analisis Miskonsepsi melalui tes Diagnostik two-tier pada materi tumbuhan kelas IV SD - Putri, Amanda Destyana; Kurniawati, Wahyu (Universitas Muhammadiyah Magelang, 2025)
This research aims to determine the misconceptions or misunderstandings that occur in class IV students in understanding plant material through the application of a two-tier diagnostic test. The research used descriptive quantitative with a case study approach, involving fourth grade students at Kasongan Elementary School as research subjects. Data collection was carried out through diagnostic tests, observations and interviews. The research results revealed that the concept of photosynthesis experienced the highest misconception with a percentage of 60%, followed by plant parts at 54.55% and plant reproduction at 50.91%. The main factors causing misconceptions are the use of less varied teaching materials and a lack of innovation in learning. These findings emphasize the importance of routinely using diagnostic evaluation tools to detect students' conceptual misunderstandings.